Pengaruh Kinerja Keuangan Berdasarkan Return On Asset (Roa), Return On Equity (Roe), Beban Operasional Pendapatan Operasional (Bopo), Financing To Deposit Ratio (Fdr) Terhadap Pengeluaran Zakat Bank Umum Syariah Indonesia - mustafidah, wiwit; Dimas Arisandi (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
The aim of this research is to determine whether there is a significant influence on financial performance based on ROA, ROE, BOPO, and FDR on the expenditure of zakat funds in Indonesian sharia commercial banks partially and simultaneously. This type of research uses quantitative methods. The population and sample taken in this research are Indonesian sharia commercial banks which issue annual financial reports which are published on their respective websites. This research uses secondary data obtained on the websites of each bank. The data analysis technique uses multiple linear regression analysis. The results of this research show that ROA and ROE do not have a significant influence on the expenditure of zakat funds from Sharia commercial banks in Indonesia, while BOPO and FDR have a significant influence. Simultaneously, the variables ROA, ROE, BOPO and FDR have a significant influence on the expenditure of zakat funds from Sharia commercial banks in Indonesia.